Cooperation, technology, and Japanese development : - Doane, Donna L. (Westview Press, 1998)
Japan is an example of what is known as a “latecomer” in industrial development. Drawing on case studies of computer and telecommunications and related firms, Donna Doane investigates how intra- and inter-industry cooperation between public and private enterprises pushed rapid technological advancement in Japan. The book places such interlinkage in the context of a historical evolution, starting with prewar industrial house groupings that helped link indigenous and external ideas and form an integrated technological base.Doane focuses mainly on the postwar, catch-up period from the 1960s through the 1980s in which three characteristics associated with late development are examined: multistructured industry, family-based industrial networks, and a distinct government-industry relationship. Implications of the cooperative structure are drawn for other advanced industrial as well as developing countries, where flexible technological networks could help individual enterprises overcome the limitations of isolated organization to survive rapid economic changes.